Protein C antigen levels in tuberculosis - Kanra, Güler; Ecevit, İ. Zafer and Seçmeer, Gülten and Tuncer, Serdar and Ceyhan, Mehmet and Mutluay, Neslihan and Başay, Nihal (The Turkish Journal of Pediatrics, 1997)
-